2005
DOI: 10.1007/s00540-005-0338-9
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuates oxidant-induced acute lung injury in an isolated perfused rabbit-lung model

Abstract: Propofol attenuates oxidant-induced ALI in an isolated perfused rabbit lung model, probably due to its antioxidant action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Specifically, we have previously shown that systemic lipid oxidation during IIR mediates altered lipid metabolism and increased alveolocapillary permeability in the lung [4]. Based on these results, we investigated propofol as a preventive agent because of its potent ability to inhibit lipid oxidation and suppress lipid metabolism [12,21] . Indeed, propofol was efficient in restoring TBARS levels to the baseline values, thus providing important antioxidant protection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, we have previously shown that systemic lipid oxidation during IIR mediates altered lipid metabolism and increased alveolocapillary permeability in the lung [4]. Based on these results, we investigated propofol as a preventive agent because of its potent ability to inhibit lipid oxidation and suppress lipid metabolism [12,21] . Indeed, propofol was efficient in restoring TBARS levels to the baseline values, thus providing important antioxidant protection.…”
Section: Discussionmentioning
confidence: 97%
“…Propofol (2, 6-diisopropyl phenol) is a commonly used intravenous anesthetic that is chemically similar to a-tocopherol and possesses potent antioxidant properties [9]. In addition to its ability to specifically counteract ischemia/reperfusion-induced lipid peroxidation [10,11], propofol also attenuates lung injury from both direct and remotely produced oxidants [12,13]. These benefits offered by propofol, along with the widespread use of the drug in the anesthetic practice, prompted us to test its efficacy in the prevention of lung injury following IIR.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol (2,6‐diisopropylphenol), an intravenous sedative–hypnotic agent popular for sedation, is chemically similar to phenol‐based free‐radical scavengers such as the endogenous antioxidant vitamin E, while its lipophilic nature allows its rapid access to cellular and subcellular membranes compartments. Propofol has been found to be effective in protecting against pathological states characterized by an increase in basal rate of ROS production in brain ( Lee et al , 2005 ), lung ( Yumoto et al , 2005 ), liver ( Tsao et al , 2003 ), testicle ( Unsal et al , 2004 ) and hearts ( Xia et al , 1996 ), but the mechanism by which it exerts the cardioprotective effect is not well established. In the current study, we propose that propofol treatment will decrease cardiac ischaemia and reperfusion injury by preservation of mitochondrial function via prevention of cardiolipin peroxidation at the mitochondrial level.…”
Section: Introductionmentioning
confidence: 99%
“…An index of Kf was determined from the changes in lung weight(LW) induced by elevated PVP as previously described[13]. During ventilation and perfusion, the PVP was rapidly elevated by 10 cm H 2 O for 7 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…The slow, and steady phase of LW gain as a function of time (ΔW/ΔT) was plotted on a semi-logarithmic scale and then extrapolated to time zero to obtain the initial rate of trans-capillary filtration. From this plot, Kf was defined as the y-intercept (gm/min) divided by PVP (10 cm H 2 O) and LW (gm), and expressed in whole units of grams per minute per centimeter of H 2 O multiplied by 100 g[13]. …”
Section: Methodsmentioning
confidence: 99%